Loneliness and older adults: psychological resilience and technology use during the COVID-19 pandemic—a cross sectional study - Balki, Eric; Hayes, Niall; Holland, Carol (Frontiers in Aging, 2023)
Introduction: This study investigated how psychological resilience influenced greater technology use among older adults, and whether they moderated the impact of social isolation on loneliness during the COVID-19 pandemic. We also explored whether technology mediates the impact of psychological resilience on loneliness. To explain the relationship between variables, the research drew upon the socio-emotional selective theory, which posits the notion that older adults are more focused on current and emotionally important relationships and goals concerning emotional regulation goals such as psychological well-being. Methods: Using a cross-sectional observational design, data were collected from 92 residents aged 65 to 89 in England from March 2020 to June 2021. Participants completed the Connor–Davidson Resilience Scale, Technology Experience Questionnaire, UCLA Loneliness Scale, and Lubben Social Network Index. Pearson correlation, mediation and moderation analyses were conducted to investigate the hypotheses. Results: Most participants experienced moderate to severe levels of loneliness, displaying higher levels than pre-pandemic. Psychological resilience predicted greater technology use, and lower levels of loneliness. Technology was found to mediate the relationship between psychological resilience and loneliness. Neither technology use, nor psychological resilience was found to moderate the impact of social isolation on loneliness. Discussion: Findings suggested that strategies directed towards screening older adults for psychological resilience levels and low technology experience may help identify those most at risk for adapting poorly when exposed to stressors in situations like the Covid-19 pandemic. Early interventions can be initiated to increase psychological resilience and technology use, including empirical interventions, that may help decrease loneliness, especially in times of elevated risks for loneliness.